PENGARUH PANJANG ENTRES TERHADAP KEBERHASILAN SAMBUNG PUCUK DAN PERTUMBUHAN BENIH JAMBU METE - Yulius Ferry; Saefudin Saefudin (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The research was to obtain proper length of upper stem to the success rate of grafting and grwoth of the seedling cashew nut plants have been conducted in the Garden Experiments Cikampek, Karawang regency, West Java. Soil types was rocky laterite andesite, type C climate and altitude of 50 meters above sea level. The research was conducted in August 2009 until April 2010. While the materials used cashew seed type B 02 for both rootstock and to the upper stem. Grafting was done after 3 months old seedlings with seedlings about 60 cm high and 0.6 cm diameter stems of seedlings. Experiments prepared following the randomized block design was repeated three times that consisting of 10 plants. The treatments were tested namely long scion 10, 15 and 20 cm. Plants grew in polybags with size 15 x 25 cm. The indicators were observed covering the base of the cuttings scion diameter, cutting the base color of entres, the percentage of shoots continued success, increased plant height, leaf number and stem diameter of the seed.The results showed that the length of entres effect on continued success grafting of seedling cashew. Scion length was 20 cm which gave the highest grafting success is as much as 78%.